2017
DOI: 10.1248/bpb.b17-00308
|View full text |Cite|
|
Sign up to set email alerts
|

New Insights into the Role of Basement Membrane-Derived Matricryptins in the Heart

Abstract: The extracellular matrix (ECM), which contributes to structural homeostasis as well as to the regulation of cellular function, is enzymatically cleaved by proteases, such as matrix metalloproteinases and cathepsins, in the normal and diseased heart. During the past two decades, matricryptins have been defined as fragments of ECM with a biologically active cryptic site, namely the 'matricryptic site,' and their biological activities have been initially identified and clarified, including anti-angiogenic and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 154 publications
(230 reference statements)
0
7
0
Order By: Relevance
“…Cleavage product of collagen IVα2 by MT1-MMP and MT2-MMP [166]. Expression is decreased 1-day post-MI [174].…”
Section: Canstatinmentioning
confidence: 98%
See 3 more Smart Citations
“…Cleavage product of collagen IVα2 by MT1-MMP and MT2-MMP [166]. Expression is decreased 1-day post-MI [174].…”
Section: Canstatinmentioning
confidence: 98%
“…This term is only used in referring to biologically active fragments that contain a cryptic domain that is not normally exposed in the intact molecule (Table 3). Matricryptins such as endostatin and tumstatin are naturally occurring fragments of basement membrane (non-fibrillar) collagens XVIII and IV, respectively, and have been reported to possess biological functions such as anti-angiogenic effects, and are associated with various diseases including cardiovascular diseases [165,166]. However, the function of endostatin remains controversial.…”
Section: Matricryptins Can Regulate Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have focused on the degradative properties of inflammatory proteases due to their significantly elevated levels in ulcerative colitis patients; however, our data suggest inflammatory proteases may be directly regulating cellular processes in a nondestructive, targeted manner via the creation of unique peptide signatures, creating new functional reactomes and protease web interactions. Indeed, while the role of bioactive peptides from extracellular matrix proteins and their contributions to tissue repair and homeostasis have been well established in skin and cardiac studies, few studies have examined the larger contributions of small peptide molecules and proteolytic regulation of tissue repair and homeostasis in other organ system. At least one study has identified significant basement matrix remodelling in ulcerative colitis as a result of altered proteolytic activity, which is consistent with our results, and degradation of therapeutic biologic antibodies by host proteases has been shown to be a potential cause for nonresponse in UC patients, although the implications of epithelial remodelling by proteases remains to be better characterized.…”
Section: Discussionmentioning
confidence: 99%